UPAYA PEMBERDAYAAN MASYARAKAT MELALUI PELAYANAN SOSIAL BAHASA INGGRIS - Akhmad Munif Mubarok; Azizatul Munafisah (UIN Sunan Kalijaga Yogyakarta, 2019)
English language institutes make various empowerment efforts to encourage community participation so they have the ability to achieve a prosperous standard of living. Empowerment efforts undertaken by English language course institutions in Pelem Village have made the community aware of the potential, have the ability to access welfare and change existing barriers. The description is the main attraction to examine how efforts to empower the community through social service institutions English courses in the Village of Pelem, Pare District, Kediri Regency. The purpose of this research is to find out, describe and analyze efforts to empower the community through social service institutions of English courses in Pelem Village, Pare District, Kediri Regency. This research uses a case study approach with qualitative research type. The technique of determining the informant using the subjectivity of researchers and the technique of determining the location using purposive.Data collection techniques using observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data display and verification. The results showed that the role of the course institutions could improve the welfare of the people of Pelem Village.Keywords: Empowerment Efforts, Institutions and community